Quality of care for children with upper respiratory infections at Mexican family medicine clinics - Svetlana V. Doubova; Ricardo Perez-Cuevas; Dulce Alejandra Balandrán-Duarte; Mario E. Rendón-Macías (Permanyer, 2015)
Background: Upper respiratory infections are the principal cause of morbidity in children <5 years of age. The objectives of this study were (i) to develop quality-of-care indicators for evaluation of care for children with upper respiratory infections (URI) at the primary care level using data from the electronic health records and (ii) to evaluate the quality of URI care offered to children <5 years of age at family medicine clinics (FMCs). Methods: Development of indicators following the RAND-UCLA method was used. A cross-sectional analysis of quality of care provided for children with URI in four FMCs in Mexico City where 10,677 children <5 years of age with URI participated. The source of information was data from 2009 electronic health records. Quality of care was evaluated using six indicators developed in the first stage of this study. Results: The quality of care evaluation identified that only 15% of children had registries of intentional search of respiratory distress signs and 27% received information on warning signs. More than 61% of children diagnosed with uncomplicated and nonstreptococcal URI received antibiotic prescription during the first visit. In the case of children diagnosed with streptococcal pharyngitis or tonsillitis, 57.5% received the appropriate antibiotic. On average, the percentage of recommended care received was 47.2%. Conclusions: It is reasonable to promote the use of electronic health records to routinely evaluate the quality of URI care. It is necessary to consider quality flaws that were found in order to endorse strategies aimed at strengthening the technical capacity of health personnel to exercise evidence-based clinical practice.